2017
DOI: 10.18632/oncotarget.22920
|View full text |Cite
|
Sign up to set email alerts
|

The novel ATM inhibitor (AZ31) enhances antitumor activity in patient derived xenografts that are resistant to irinotecan monotherapy

Abstract: Irinotecan, a standard of care therapy for CRC, elicits cytotoxic effects by generating double strand breaks resulting in DNA damage. The activation of the ATM pathway plays a fundamental role in regulating the cellular response and repair to DNA damage. The objective of this preclinical study was to determine whether ATM inhibition would enhance sensitivity to irinotecan treatment. Treatment effects of AZ31, irinotecan or AZ31 + irinotecan were investigated in CRC cell lines and CRC patient derived xenografts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…This compound was shown to inhibit downstream ATM phosphorylation after radiation, and it also enhanced responses to the topoisomerase inhibitors etoposide, camptothecins, and doxorubicin (73). A similar sensitization to topoisomerase inhibitors was later demonstrated with the ATM inhibitor AZ31, which was shown to increase the efficacy of irinotecan in resistant tumors in PDX models (74). KU60019 is another compound that was introduced in 2009 as an improved analogue of KU55933 (75), and early work demonstrated that KU60019 is a potent radiosensitizer (75).…”
Section: Atm Inhibitorsmentioning
confidence: 72%
“…This compound was shown to inhibit downstream ATM phosphorylation after radiation, and it also enhanced responses to the topoisomerase inhibitors etoposide, camptothecins, and doxorubicin (73). A similar sensitization to topoisomerase inhibitors was later demonstrated with the ATM inhibitor AZ31, which was shown to increase the efficacy of irinotecan in resistant tumors in PDX models (74). KU60019 is another compound that was introduced in 2009 as an improved analogue of KU55933 (75), and early work demonstrated that KU60019 is a potent radiosensitizer (75).…”
Section: Atm Inhibitorsmentioning
confidence: 72%
“…We anticipate that AZD0156 will also potentiate the effects of other clinically relevant DSB-inducing agents such as topoisomerase inhibitors (e.g., irinotecan and topotecan; refs. 21,38).…”
Section: Discussionmentioning
confidence: 99%
“…5A, right panel). To directly assess the importance of ATM kinase activity (66,69,70) in HSATII RNA induction the effect of Ku-55933 or AZ31, ATM kinase inhibitors (71,72), were tested. Neither drug compromised the viability of ARPE-19 cells when tested at concentrations up to 50 µM (Fig.…”
Section: Zeocin Treatment Substantially Mimics the Transcriptional Efmentioning
confidence: 99%
“…5B, left panel). However, because we noticed morphological changes in treated cells at the highest dose (50 µM), we used Ku-55933 and AZ31 at 20 µM, which is in the range of concentrations at which these drugs are typically used (71)(72)(73). Cells were pretreated with Ku-55933 or AZ31 for 2 h before being treated with zeocin (100 µg/mL).…”
Section: Zeocin Treatment Substantially Mimics the Transcriptional Efmentioning
confidence: 99%